High seroprevalence of Strongyloides stercoralis among individuals from endemic areas considered for solid organ transplant donation: A retrospective serum-bank based study. - Joan Gómez-Junyent; David Paredes; Juan Carlos Hurtado; Ana Requena-Méndez; Angel Ruiz; Maria Eugenia Valls; Jordi Vila; Jose Muñoz (Public Library of Science (PLoS), 2018)
Background Strongyloides stercoralis is a worldwide disseminated parasitic disease that can be transmitted from solid organ transplant (SOT) donors to recipients. We determined the serological prevalence of S. stercoralis among deceased individuals from endemic areas considered for SOT donation, using our institution's serum bank. Methodology Retrospective study including all deceased potential donors from endemic areas of strongyloidiasis considered for SOT between January 2004 and December 2014 in a tertiary care hospital. The commercial serological test IVD-Elisa was used to determine the serological prevalence of S. stercoralis. Principal findings Among 1025 deceased individuals during the study period, 90 were from endemic areas of strongyloidiasis. There were available serum samples for 65 patients and 6 of them tested positive for S. stercoralis (9.23%). Only one of the deceased candidates was finally a donor, without transmitting the infection. Conclusions Among deceased individuals from endemic areas considered for SOT donation, seroprevalence of strongyloidiasis was high. This highlights the importance of adhering to current recommendations on screening for S. stercoralis among potential SOT donors at high risk of the infection, together with the need of developing a rapid diagnostic test to fully implement these screening strategies.